Algorithmic Hegemony and the Political Economy of Digital Media: The Commodification of Political Content on Deddy Corbuzier's YouTube Channel - Khoirul Hudah; Luxy Nabela Farez (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Digital transformation has reshaped media ecosystems by positioning YouTube as a dominant platform for producing, distributing, and consuming content within the logic of algorithmic capitalism. However, studies examining how political content creators negotiate power relations within this digital environment, particularly in Indonesia, remain limited. Addressing this gap, this research aims to analyze the political economy practices embedded in Deddy Corbuzier’s “Close The Door” YouTube program using Vincent Mosco’s framework of commodification, spatialization, and structuration. Employing an interpretive qualitative approach, the study investigates ten episodes featuring national political actors published in 2022-2025. Data were collected through digital documentation and analyzed using Miles, Huberman, and Saldaña’s interactive model. The findings reveal that political discussions on the channel are transformed into economic commodities through monetization systems, algorithmic visibility, and high audience engagement. Spatialization emerges through YouTube’s recommendation infrastructure and global data networks that link local content creators with multinational corporate interests such as Google. Structuration is reflected in the reciprocal yet asymmetrical interactions among creators, platforms, audiences, and political elites, collectively shaping symbolic power in the digital sphere. The study concludes that YouTube functions not only as an alternative media space but also as a hegemonic arena governed by digital capitalist logics. These results provide theoretical contributions to the political economy of media in Indonesia and offer practical insights into how algorithmic systems increasingly shape public discourse and redistribute power away from traditional media institutions.